2011
DOI: 10.1111/j.1463-6395.2010.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of morphology and histology of the alimentary tract of Glyptosternum maculatum (Sisoridae, Siluriformes)

Abstract: 2011. A study of morphology and histology of the alimentary tract of Glyptosternum maculatum (Sisoridae, Siluriformes). -Acta Zoologica (Stockholm) 92: 161-169.The structure of alimentary tract has been studied in a cold water fish Glyptosternum maculatum, an endemic teleost species of notable economic importance and with high potential for controlled rearing of the species in Tibet, by light and electron microscope. Glyptosternum maculatum has short oesophagus, large caecal-type stomach and short intestine, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
73
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(91 citation statements)
references
References 27 publications
(83 reference statements)
15
73
1
2
Order By: Relevance
“…This difference between P. maculatus and T. striatulus is consistent with omnivorous feeding habits that tend KAPOOR et al (1975), they produce mucus and are primary food detectors. Trachelyopterus striatulus presented a stratified squamous epithelium with taste buds, as observed in Glyptosternum maculatum (Regan, 1905) (XIONG et al 2011). Histochemical analyses of this study showed neutral mucus, carboxylic and sulphated acids, which, according to AGRAWAL & MITTAL (1992), are important in labial epithelium lubrication and protection.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…This difference between P. maculatus and T. striatulus is consistent with omnivorous feeding habits that tend KAPOOR et al (1975), they produce mucus and are primary food detectors. Trachelyopterus striatulus presented a stratified squamous epithelium with taste buds, as observed in Glyptosternum maculatum (Regan, 1905) (XIONG et al 2011). Histochemical analyses of this study showed neutral mucus, carboxylic and sulphated acids, which, according to AGRAWAL & MITTAL (1992), are important in labial epithelium lubrication and protection.…”
Section: Discussionsupporting
confidence: 72%
“…In fact, eating insects like coleopterans, as described for the species under study (DIAS et al 2005), can cause injury to the oesophageal tissue, but the epithelium protects this layer. Mucous cells were observed in the oesophageal epithelium of T. striatulus, and they reacted positively to histochemical analysis, similar to P. maculatus (GODINHO et al 1970) and T. brasiliensis (OLIVEIRA-RIBEIRO & FANTA 2000), suggesting that this action of the mucus is associated to guiding different types of prey and lubricating the food, also described by OLIVEIRA- RIBEIRO & FANTA (2000) and XIONG et al (2011). Taste buds were observed in the oesophageal epithelium of T. striatulus and in the Siluriformes I. punctatus (SIS et al 1979), T. brasiliensis (OLIVEIRA-RIBEIRO & FANTA 2000), and G. maculatum (XIONG et al 2011).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Microscopically, in the great majority of fish species, intestinal wall is described by three (Çinar & Şenol, 2006) or four tunics (Olaya et al, 2007;Wilson & Castro, 2011;Xiong et al, 2011), depending on whether the tunica submucosa is considered together with the tunica mucosa or not.…”
mentioning
confidence: 99%